NEGOTIATING COMMON GROUND IN COMPUTER-MEDIATED VERSUS FACE-TO-FACE DISCUSSIONS - Ilona Vandergriff (Language Learning and Technology, 2006)
To explore the impact of the communication medium on building common ground, this article presents research comparing learner use of reception strategies in traditional face-to-face (FTF) and in synchronous computer-mediated communication (CMC).Reception strategies, such as reprises, hypothesis testing and forward inferencing provide evidence of comprehension and thus serve to establish common ground among participants. A number of factors, including communicative purpose or medium are hypothesized to affect the use of such strategies (Clark & Brennan, 1991). In the data analysis, I 1) identify specific types of reception strategies, 2) compare their relative frequencies by communication medium, by task, and by learner and 3) describe how these reception strategies function in the discussions. The findings of the quantitative analysis show that the medium alone seems to have little impact on grounding as indicated by use of reception strategies. The qualitative analysis provides evidence that participants adapted the strategies to the goals of the communicative interaction as they used them primarily to negotiate and update common ground on their collaborative activity rather than to compensate for L2 deficiencies.